Optimal Lung Inflation Techniques in a Rat Lung Transplantation Model: A Revisit - Tanaka, Yugo; Shigemura, Norihisa; Noda, Kentaro; Kawamura, Tomohiro; Isse, Kumiko; Stolz, Donna B.; Bermudez, Christian A. (The Thoracic and Cardiovascular Surgeon, 2014)
Background Most of the experimental work assessing optimal lung inflation during lung graft preservation was performed in the late 1990s. Since that time, lung preservation before transplantation has been more standardized, and the optimal lung inflation techniques used during lung preservation in the current clinical setting remain undefined. Nonetheless, lung inflation during storage may play a pivotal role in optimal lung preservation.Materials and Methods Lewis rat lungs were perfused with and stored in cold, low-potassium dextran solution (Perfadex, Vitrolife, Göteborg, Sweden) for 6 hours at different levels of lung inflation (25, 50, 75, or 100% of vital capacity [VC]). Orthotopic left lung transplantation using cuff techniques was performed in syngeneic Lewis rats. Posttransplant allograft function, expression of proinflammatory mediators, and expression of lung surfactants were evaluated.Results Lungs inflated to 75 or 100% VC showed a significantly better oxygenation in blood gas analysis than lungs inflated to 25 or 50% VC. The levels of mRNAs for tumor necrosis factor-α, pro-interleukin-1β, intracellular adhesion molecule 1 were attenuated in lungs inflated to 75 or 100% VC as compared with deflated lungs, suggesting reduced ischemia/reperfusion injury. In addition, transmission electron microscopy demonstrated better preserved lung surfactants in the alveolar space in the lungs inflated to 75 or 100% VC.Conclusions Inflating lungs to 75 or 100% VC during preservation may be beneficial and result in better posttransplant allograft function through attenuated reperfusion injury and better preserved lung surfactants.
Keywords: organ preservation; transplantation; lung; ischemia/reperfusion